Formulation and standardisation of jack fruit functional candy - Ray, Babu R M; Narasaiah T, Bala; Suresh, Challa (Journal of Postharvest Technology, 2021)
The jack fruit (Artocarpus heterophyllus Lam) is a multi-purpose tree that provides food, fodder, timber, fuel. Both immature and mature fruits  are consumed in different local dishes; soft-type ripe fruits remain underutilised due to poor shelf life despite their immense potential. The present  investigation developed fruit-based hard candy that showed better acceptability, storage stability for more than 10months, rich mineral  composition, and consumer safety. The study proved that it is possible to convert jackfruit pulp into functional candies instead of wastage. The  water activity(aw) ranged from 0.46 to 0.58 during 14 months of ambient storage and was found acceptable. The nutritional composition were  moisture (2.45g/100g), protein (1.30g/100g), total ash (0.59g/100g), carbohydrates(94.57g/100g) and energy (393.30 K.Cal/100g). Calcium  (42.38mg/kg), Potassium (3309.42mg/kg), Magnesium (263.75mg/kg), and Sodium (239.08mg/kg). Among the trace minerals, Chromium (2.04mg/kg), Copper (3.00mg/kg), Iron (40.19mg/kg), Gallium (0.155mg/kg), Manganese (2.47mg/kg) and Zinc (3.64mg/kg). Others elements  like Lithium(0.04mg/kg), Gallium (0.15mg/kg), cobalt (0.05mg/kg), Cadmium(0.007mg/kg), Barium(1.02mg/kg), Silver (0.02mg/kg), Nickel (0.31mg/kg) and Strontium (0.59 mg/kg) found in traces and Bismuth, Indium and Thallium was found below the detection limits. The process  is cost-effective to converts waste into a new product range of longer shelf-life.
Keywords: Hard-boiled candy; functional fruit candy; jack fruit candy